PENGARUH KERAMAHAN, KREDIBILITAS DAN CITRA KARYAWAN TERHADAP KEDEKATAN KARYAWAN DAN KEPUASAN NASABAH PRODUK TABUNGAN BANK KONVENSIONAL DI SURABAYA - Chairun Nisa Halim; Tatik Suryani (Journal of Business & Banking, 2013)
Banks as financial institutions have delivered superior services to their customers for gaining competitive advantages. The intimacy between banks employees and customers has signifi- cant role for creating satisfaction. This research tries to examine the influence of the deter- mination of customer intimacy specifically benevolence, credibility, and image of banks em- ployee on intimacy between banks employees and customers and customer satisfaction. Re- search involved 100 customers from four banks (Mandiri, BNI, BRI, and BTN) that selected by purposive sampling. Data were analyzed by Structural Equation Modeling (SEM). The results showed that: (1) benevolence did not have significantly effect on intimacy between banks employees and customers, (2) credibility and employees image have significantly in- fluences on intimacy between banks employees and customers, and (3) bank s employees and customers intimacy has positive effect on customer satisfaction. The implication of this research is that bank should improve the credibility and employee image for creating banks employees and customers intimacy. Beside it, bank should keep their intimacy for satisfying the customers.